"Her Anger Frightens Me!" Using Group-Work Practice Principles and Feature Films in Teaching Clinical Practice in Mental Health. Issue 3 (3rd July 2018) - Fleischer, Les
ABSTRACT: Combining group-work practice principles and the arts (feature films) can contribute to more effective teaching and enhance student clinical practice competency. By treating teaching as a form of group work and introducing a feature film into the classroom group, an instructor can reduce student-learning anxieties, teach core clinical concepts and skills, and enhance the classroom's socioemotional climate. Vignettes demonstrate how this approach to teaching enriched students' learning in an introductory clinical social work class on adult mental health.